Pengaruh Daya Tarik Wisata Terhadap Pendapatan Petani di Kawasan Wisata Kambo, Kota Palopo - Muhammad Syihab Zainuddin; Sulfiana Sulfiana; Helda Ibrahim (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The Kambo tourist area in Kambo Village, Mungkajang District, Palopo City, is a rapidly developing natural tourist destination and was designated a leading tourist village in 2022. This area is characterized by highlands, natural panoramas, and agricultural potential in the form of coffee, cocoa, cloves, galangal, trigona honey, and tropical fruits. Tourism activities in this area open up new economic opportunities for farmers, such as selling agricultural products directly to tourists, local culinary businesses, and providing parking and other tourism services. This study aims to analyze the effect of tourist attractions on farmers’ income in the Kambo tourism area, Palopo City. Tourist attraction is measured through three variables, namely natural beauty, tourism facilities, and accessibility. The study employs a quantitative approach with an explanatory research design. Data were collected through a survey using questionnaires administered to 30 farmers selected using a saturated sampling technique. Data analysis was conducted using multiple linear regression, accompanied by classical assumption tests, t-tests, F-tests, and the coefficient of determination. The results show that natural beauty and accessibility have a positive and significant effect on farmers’ income, while tourism facilities do not have a significant partial effect. Simultaneously, the three variables significantly affect farmers’ income, with a coefficient of determination of 66.9%. These findings indicate that the quality of natural scenery and ease of access are the main factors in encouraging farmers’ economic activities through the tourism sector. Therefore, the development of the Kambo tourism area should be directed toward improving environmental quality and accessibility infrastructure, as well as integrating tourism facilities with farmers’ economic activities to ensure more optimal and sustainable economic impacts.